Lusophony within Central Africa in the pre-colonial era. A contribution to its history and understanding today - Heintze, Beatrix (2016)
Since the arrival of the Portuguese in the 15th century the spread of the Portuguese language across Angola has primarily been linked with the Atlantic slave trade. The main impulses are regarded as radiating from Portuguese settlements along the coast and in the hinterlands, as well as from their military posts and trading stations. However, it would be too reductionistic to assert that the historical roots of present-day Lusophone culture is of Portuguese provenience only and the product of colonial rule. As early as the 17th century Africans began adopting elements of Portuguese culture – dress certainly, but most importantly the written and spoken language – not only in areas of the coastal hinterland, but beginning in the 19th century also deep in the continent’s interior well out of reach of any direct Portuguese influence. This too played a decisive role in the spread of Lusophone culture. In the African interior this process was interrupted after the Berlin Conference and the establishment of the Congo Free State. However, in the western regions this process, propelled and sustained by Portuguese, Luso-Africans and a few Africans, laid the foundations early on for what would later become a flourishing Lusophone culture.